Оптимальне оцінювання параметрів стану об’єкта управління за експоненціально-квадратичним критерієм якості - Іващенко, М. І.; Лобок, О. П. (Видавництво Львівської політехніки, 2011)
The solution of the problem of estimation of parameters for controlled objects by using exponent-quadratic criterion is offered in this paper. The object is described as a State Space object. The external perturbations are Wiener processes.
Keywords: optimal estimation; exponent-quadratic criterion; external random perturbations